(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Foreign Direct Investment (FDI) plays a critical role in the Indian financial system’s rural sector. In order to boost the notion of yields, FDI is allowed in the growing part. Since 2010, FDI inflows to the agricultural sector of the Indian economy have increased significantly. Agriculture is regarded to be the nation’s foundation, and it employs 65 percent of the Indian population